(NsTRESS I POSTSTRESSOWYE RASSTROJSTWA (B:s (NlI^NOSTX I OB]ESTWO (B/s - (NsUKIASQN(B, (NsAMWEL gRANTOWI^s; (NtADEWOSQN(B, (NaDA sEMENOWNAs; (N~[MARITQN(B, (NsAMWEL sERGEEWI^s; (NmANASQN(B, (NnARINE gEORGIEWNAs ((NeREWAN (B:s (NaSOGIK(B,s, 2003)
(NrEZ(B.: (NANGL(B.s
(NbIBLIOGR(B.: (NS(B. 314-340s
Keywords: (NsTRESS (B- (NwLIQNIE NA ORGANIZMs -- (NpRI^INY(B, (NMEHANIZMY(B, (NPROQWLENIQs; (NpOSTSTRESSOWYE RASSTROJSTWAs -- (NlE^ENIEs; (NlI^NOSTX I OB]ESTWOs; (NpSIHOLOGIQs; (N|KSTREMALXNYE SITUACII I KATASTROFYs